Hubungan Antara Loyalitas dan Perceived Organizational Support dengan Work Engagement pada Petugas Pelayanan Kantor Ditlantas Polda Daerah X - Nur Fauzi Alfajar (LPPM Universitas Proklamasi 45, 2020)
The issue of work engagement in the Ditlantas Polda X cannot be ignored. This is because as stated by Bakker & Demerouti (2008) that high work engagement can stimulate the energy and enthusiasm of organizational members at work. It was further stated that the work of individuals who have high energy and enthusiasm will certainly be better than those who have low energy and enthusiasm. This research is important, because if police members do not have work engagement, they will provide services carelessly, thus hampering the development of institutions.The data analysis method used in this study uses the Pearson product moment correlation statistical test and multiple correlations. Pearson product moment correlation analysis is one of several types of correlation tests used to determine the degree of closeness relationship between 2 or more variables that are interval or ratio scale, which with this test will return the value of the correlation coefficient whose values range between -1,0 and 1. A value of -1 is means a perfect negative correlation, 0 is means no correlation and 1 is means a perfect positive correlation.The results of this study indicate that the 64% correlation value of the work engagement variable is shown together (simultaneously) by the correlation between the loyalty variable and perceived organizational support. The data shows that there are still 36% of work engagement variables that are supported by variables or other aspects such as: culture in the workplace, organizational communication, managerial style that triggers trust and appreciation, leadership and corporate reputation itself, characteristics organizational (Lockwood, 2007).